Use of a Potential Probiotic, Lactobacillus casei L4, in the Preparation of Fermented Coconut Water Beverage - Giri, Sib S.; Sukumaran, Venkatachalam; Sen, Shib S.; Park, Se Chang (Frontiers in Microbiology, 2018)
Coconut water (CW) is a clear, nutritive liquid found as the coconut endosperm of green coconuts such as Cocos nucifera L., and its widespread consumption owes to its unique composition of sugars, minerals, vitamins, enzymes, and hormones. Probiotic fermentation of CW may facilitate the development of an improved functional beverage with probiotic benefits; therefore, we aimed to produce a fermented CW beverage using the potential probiotic Lactobacillus casei L4. CW was fermented with Lactobacillus casei L4 for 48 h at 35ºC, and the pH, organic acid-production rate, antioxidant activity, antibacterial activity, sugar, mineral, vitamin B12 levels, and total viable bacteria counts were investigated at 24 and 48 h. We demonstrated that the fermentation of CW with probiotic lactobacilli increased the cell viability count. Vitamin B12 production was highest in the extracellular environment at 48 h (11.47 μg/mL), while the total phenolic content was significantly (p < 0.05) higher in the fermented CW at 48 h (72.1 μg/mL gallic acid equivalents) than observed with the other investigated groups or time points. The fermented materials exhibited the highest 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical-scavenging activities at 48 h (58.4% and 69.2%, respectively). The levels of most minerals remained unchanged in the fermented CW, except for calcium, manganese, phosphorus, and sodium. Furthermore, the culture supernatant from fermented CW inhibited the growth of foodborne pathogens such as Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus, and Salmonella typhi, although the degree of inhibition varied between the species. Moreover, adding 15% honey and artificial coconut flavor to the fermented CW resulted in a better-tasting product, as demonstrated by a sensory-evaluation test. The obtained results indicated that the CW product fermented by Lactobacillus casei L4 may be used as a novel functional beverage containing both electrolytes and probiotics, and can serve as a good vehicle for preparing a wider range of novel products.